Constitutions and gender - Irving, Helen (Research handbooks in comparative law, 2017)
The idea that constitutions are gendered is not new, but its recognition is the product of a revolution in thinking that began in the last decades of the twentieth century. As a field, it is attracting scholarly attention and influencing practice around the world. This timely Handbook features contributions from leading pioneers and younger scholars, applying a gendered lens to constitution-making and design, constitutional practice and citizenship, and constitutional challenges to gender equality rights and values. Offering a cutting-edge perspective on the constitutional text and record of multiple jurisdictions, from long-established to newly emerging democracies, Constitutions and Gender portrays a profound shift in our understanding of what constitutions stand for and what they do.-